Optimization of iron-enhanced anaerobic digestion of agro-wastes for biomethane production and phosphate release. Issue 5 (23rd February 2023) - Ugwu, Samson Nnaemeka; Enweremadu, Christopher Chintua
ABSTRACT: In this study, the optimization of additives (polypyrrole magnetite nanocomposites (Ppy/Fe3 O4 ) and antagonists (humic acid and arsenic oxide)) for simultaneous recovery of biomethane and phosphate release from enhanced anaerobic co-digestion of okra waste and pig manure was investigated. The pre-determined dosages of additives from our previous studies were used for the batch anaerobic digestion at different ratios under mesophilic conditions based on the two level-four factors central composite design (CCD) response surface methodology (RSM). After the anaerobic digestion processes, the biomethane yields were recorded and the digestates were characterized to determine the quantity of soluble phosphates. Both the independent variables and the responses were used to model and optimize the biogas yield and phosphate release conditions. The result showed that the maximum biomethane yield and P release were respectively 502.743 mLCH4/gVS and 168.674 mg/L at the optimum conditions of Ppy/Fe3 O4 (20.0014 mg/L), HA (5.0018 mg/L), As (1.448 mg/L) and co-digestion (25.0001%). The response models predicted biomethane yield and P release to be 528.635 mLCH4/gVS and 164.405 mg/L respectively. All the response models were highly significant with appropriate goodness of fit and had prediction differences of 4.90% and 2.597% respectively for both biomethane yield and P release. Although both the accelerants and antagonists had influences on the anaerobic digestion processes by achieving enhanced biomethane production and P release, the influence of long exposure of anaerobic digestion processes to these additives on both responses is recommended for further investigation. GRAPHICAL ABSTRACT: UF0001